2017
DOI: 10.1093/neuros/nyx164
|View full text |Cite
|
Sign up to set email alerts
|

Early Venous Thromboembolism Chemoprophylaxis After Traumatic Intracranial Hemorrhage

Abstract: Early (<24 h) initiation of VTE chemoprophylaxis in patients with traumatic intracranial hemorrhage appears to be safe. Further prospective studies are needed to validate this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
0
12
1
Order By: Relevance
“…12 Other studies, albeit small and lacking generalizability, have reported no new or worsening intracranial hemorrhage in TBI patients if chemoprophylaxis is started as early as 48 hours after admission. 8,9,[13][14][15][16][17][18] Our study is the only one to date that evaluates outcomes based on 7 hour follow-up CT scan and initiation of chemoprophylaxis within 24 hours of injury. It adds to the body of evidence in this area by demonstrating that chemoprophylaxis can be safely started less than 24 hours following injury.…”
Section: Discussionmentioning
confidence: 99%
“…12 Other studies, albeit small and lacking generalizability, have reported no new or worsening intracranial hemorrhage in TBI patients if chemoprophylaxis is started as early as 48 hours after admission. 8,9,[13][14][15][16][17][18] Our study is the only one to date that evaluates outcomes based on 7 hour follow-up CT scan and initiation of chemoprophylaxis within 24 hours of injury. It adds to the body of evidence in this area by demonstrating that chemoprophylaxis can be safely started less than 24 hours following injury.…”
Section: Discussionmentioning
confidence: 99%
“…Among 94 intracranial hemorrhage patients started on chemoprophylaxis within 24 hours of admission, there was no difference in rates of radiographic expansion of the hematoma as compared with delayed chemoprophylaxis. 19 The study by Byrne et al in severe TBI patients referenced earlier also looked at safety outcomes and found no increased risk of late neurosurgical intervention or death when prophylaxis was started within 72 hours. 11 Patients with severe TBI, associated intracranial hemorrhage (ICH), and lower GCS were more likely to start chemoprophylaxis in the delayed time periods within our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients with TBI have an increased risk of VTE 63,64 , anticoagulant thromboprophylaxis is often delayed because of concerns about progression of intracranial bleeding (ICB). One study reported a greater risk of ICB associated with early anticoagulant thromboprophylaxis 65 , while the vast majority did not 33,57,62,66-71 . Among 1,803 patients with moderate or severe TBI (head Abbreviated Injury Scale > 2), those who started anticoagulant thromboprophylaxis within 48 hours after injury were three times less likely to develop VTE than those who started later without increased bleeding risk 33 .…”
Section: - What Is the Optimal Vte Prophylaxis For Polytrauma Patient...mentioning
confidence: 99%